2001
DOI: 10.1200/jco.2001.19.6.1795
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Neuroblastoma Cells Detected by Reverse Transcriptase Polymerase Chain Reaction for Tyrosine Hydroxylase mRNA Are an Independent Poor Prognostic Indicator in Stage 4 Neuroblastoma in Children Over 1 Year

Abstract: C i r c u l a t i n g N e u r o b l a s t o m a C e l l s D e t e c t e d b y R e v e r s e T r a n s c r i p t a s e P o l y m e r a s e C h a i n R e a c t i o n f o r T y r o s i n e H y d r o x y l a s e m R N A A r e a n I n d e p e n d e n t P o o r P r o g n o s t i c I n d i c a t o r i n S t a g e 4 N e u r o b l a s t o m a i n C h i l d r e n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 25 publications
5
77
0
Order By: Relevance
“…Although other targets for the detection of NB cells by RT -PCR have been described, TH mRNA is currently the single most widely evaluated target (Burchill et al, 1994;Miyajima et al, 1995;Gilbert et al, 1997;Cheung and Cheung, 2001;Tchirkov et al, 2003;Ito et al, 2004;Ootsuka et al, 2008;Träger et al, 2008). Clinically significant disease has been detected in PB (Burchill et al, 1995(Burchill et al, , 2001aKuroda et al, 1997;Shono et al, 2000;Cheung et al, 2004) and BM (Miyajima et al, 1996;Kuroda et al, 1997;Shono et al, 2000;Fukuda et al, 2001;Horibe et al, 2001) samples from children with NB at diagnosis, on therapy, during follow-up and at relapse by RT -PCR for TH. Furthermore, this technique has been used to detect NB cells in PBSC from children with high-risk disease (Miyajima et al, 1996;Burchill et al, 2001b;Corrias et al, 2006).…”
Section: Target Selection In Nbmentioning
confidence: 99%
“…Although other targets for the detection of NB cells by RT -PCR have been described, TH mRNA is currently the single most widely evaluated target (Burchill et al, 1994;Miyajima et al, 1995;Gilbert et al, 1997;Cheung and Cheung, 2001;Tchirkov et al, 2003;Ito et al, 2004;Ootsuka et al, 2008;Träger et al, 2008). Clinically significant disease has been detected in PB (Burchill et al, 1995(Burchill et al, , 2001aKuroda et al, 1997;Shono et al, 2000;Cheung et al, 2004) and BM (Miyajima et al, 1996;Kuroda et al, 1997;Shono et al, 2000;Fukuda et al, 2001;Horibe et al, 2001) samples from children with NB at diagnosis, on therapy, during follow-up and at relapse by RT -PCR for TH. Furthermore, this technique has been used to detect NB cells in PBSC from children with high-risk disease (Miyajima et al, 1996;Burchill et al, 2001b;Corrias et al, 2006).…”
Section: Target Selection In Nbmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Features associated with an improved prognosis include younger age 5,7 and absence of bone marrow involvement at diagnosis, 12 early disease response 13 and a complete or near complete response following induction therapy. 6,7,10,14 A poorer prognosis has been associated with an elevated serum ferritin (4143 ng/ ml), 6 bone and BM metastasis, 6 detectable circulating NB cells at diagnosis, 15,16 persisting skeletal and BM disease at the end of induction therapy, 1,2 circulating NB cells in patients otherwise apparently disease-free 16 and high-level of NB contamination at marrow harvest. 14,15 Intensive induction therapy and ASCT have improved the outcomes of older children and those with MYCN amplified disease.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of studies demonstrated the prognostic value of MRD in bone marrow and blood, the level of clinically significant MRD and the timing of MRD were not consistent in these studies (Burchill et al, 2001;Cai et al, 2007;I.Y. Cheung et al, 2003;Moss et al, 1991;Seeger et al, 2000;Stutterheim et al, 2011).…”
Section: Surveillance Of Minimal Residual Diseasementioning
confidence: 90%